Influence of soil tillage systems on aggregate stability and the distribution of C and N in different aggregate fractions - Kasper, Martina; Buchan, G.D.; Mentler, A.; Blum, W.E.H. (Soil & tillage research, 2009)
Soil aggregation is influenced by the tillage system used, which in turn affects the amount of C and N in the different aggregate fractions. This study assessed the impact of different tillage systems on soil aggregates by measuring the aggregate stability, the organic carbon (C org) and the total nitrogen (N tot) contents within different aggregate fractions, and their release of dissolved organic carbon (DOC). Soil samples were collected from the top 0 to 10 cm of a long-term tillage experiment at Fuchsenbigl (Marchfeld, Austria) where conventional tillage (CT), reduced tillage (RT), and minimum tillage (MT) treatments were applied to a Chernozem fine sandy loam. The stable aggregates (1000–2000 μm) were subject to dispersion by the soil aggregate stability (SAS or wet sieving) method after Kemper and Rosenau (1986), and the ultrasonic method of Mayer et al. (2002). Chemical analysis of the soil was obtained for the aggregate fractions 630–1000, 250–630 and 63–250 μm gathered from the ultrasonic method. Using the SAS method, CT and RT had the least amounts of stable aggregates (18.2% and 18.9%, respectively), whereas MT had twice as much stable aggregates (37.6%). Using the ultrasonic method, MT also had the highest amount of water stable aggregates in all three fractions (1.5%, 3.7%, and 35%, respectively), followed by RT (1%, 2.3%, 32.3%), and CT (0.8%, 1.7%, 29.1%). For comparison, a reference soil, EUROSOIL 7 (ES-7) was also analysed (40%, 6.7%, and 12.1%). The highest amounts of C org and N tot were measured under MT in all three fractions, with 8.9%, 3.8%, and 1.3% for C org, and 0.4%, 0.3%, and 0.1% for N tot. Apart from the fraction 630–1000 μm, the aggregates of RT and CT contained <50% of the C org and N tot values of MT. The C/N ratio was least favourable for CT (42.6) in the aggregate fraction 630–1000 μm. The DOC release from stable aggregates after 10 min of ultrasonic dispersion was highest from MT soil (86.7 mg l −1). The values for RT and CT were 21% and 25% below this value. The results demonstrate that tillage type influences both aggregate stability and aggregate chemical composition. This research confirms that CT interferes more with the natural soil properties than RT and MT. Furthermore, MT has the highest potential to sequester C and N in this agriculturally used soil.